(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2023)
Health Management Information System (HMIS) is a complete government web-based portal designed to manage healthcare data nationally in India. On 23rd October 2008, the government of India dispatched this national-level portal to screen the progress of the National Health Mission so that this HMIS portal could provide a structured report and monitor data over some time, which could help formulate the new national-level policy. This study was conducted through primary and secondary data collection and consisted of a graphical analysis of data observed from April 2008 to March 2020. Various stages of development of national-level HMIS were considered and studied. The Knowledge, Attitude, and Practice (KAP) levels among the Indian healthcare professionals about the Nation Health Portal were studied. Other than that, the analysis provided information on the coverage and usage of health data reporting to national-level HMIS in India. Various underlying causes for data capturing methods and errors in HMIS were identified in the study. The existing challenges and limitations regarding using HMIS were discussed based on statistical analysis and results. The exciting advancements and standardization efforts in enhancing the quality of Health Management Information Systems (HMIS) are poised soon to make a significant impact on integrating national-level data for maximizing the effectiveness of healthcare systems. India must go a long way in the race for a data-driven revolution in health care. Note that the National level Health portal is a great initiative by the government of India.